Parotid preservation or immune protection? The dual dilemma in head and neck cancer radiotherapy - Qin, Jianing; Zhang, Fengjuan; Zhang, Wenjing; Yang, Song; Yang, Bin; Xie, Tao; Zhang, Hui; Wan, Min; Li, Huachi (Frontiers in Immunology, 2025)
Head and neck cancer (HNC) represent a common category of malignant tumors. Radiotherapy, as the primary treatment modality for these tumors, while effectively controlling tumor progression, is often accompanied by a series of treatment-related side effects. As a major salivary gland in the head-and-neck region, the parotid gland (PG) is particularly susceptible to radiation damage during radiotherapy, given its anatomical proximity to the target irradiation area. The radiation dose and irradiated volume of the PG not only disrupt its physiological secretory function, leading to debilitating side effects like xerostomia and dysphagia, but also potentially compromise tumor control and patient outcomes by modulating the local and systemic immune homeostasis. This article systematically reviews the relevant research on the impact of PG irradiation on the immune microenvironment during HNC radiotherapy in recent years, and it delves into multiple levels, including cytokine changes and immune cell function alterations, aiming to offer a comprehensive theoretical basis and novel research perspectives for optimizing radiotherapy plans, reducing radiotherapy-related adverse reactions, and improving patient prognosis.